Advances in the Oral Delivery of Protein and Peptide Drugs - Guanyu Chen (Pharmaceutics)
Protein and peptide drugs (PPDs) are highly effective therapies for a wide range of diseases, including cancer, diabetes, and autoimmune disorders [...]